Slovenci, slovenski jezik in reformacija na Dravskem polju - Oman, Žiga (Slovenski jezik, 2015)
Until recently we were sure that the Reformation in the Northeast of Slovene Styria was exclusively %German%, but modern methodological approaches have lately helped with revising this view. It has been shown, that, although the district of the Augsburg Confession officially and ecclesiastically functioned in German, the Slovene speaking population from all social classes participated in the Reformation in the Dravsko polje region. It can also be shown that Slovene Protestant literature was simultaneously circulating at the local level.
Keywords: Dravsko polje; history; reformacija; Slovene; slovenščina; zgodovina